Wilhelm Backhaus photograph with autograph quotation from Beethoven's Fourth Piano Concerto - Backhaus, Wilhelm, 1884-1969:::Creator::::::::::::
Photograph of Wilhelm Backhaus, accompanied by autographed quotation for the slow movement of the Fourth Fortepiano Concerto, identified as Beethoven/Orpheus in the Underworld, with inscription "Herr Henry Effling für Erinnerung an Manchester, Wilhelm Backhaus, 27 Febr. 1902".